2000
DOI: 10.4049/jimmunol.164.12.6100
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Soluble HLA-G1 Triggers CD95/CD95 Ligand-Mediated Apoptosis in Activated CD8+ Cells by Interacting with CD8

Abstract: The nonpolymorphic soluble HLA-G1 (sHLA-G1) isoform has been reported to be secreted by trophoblast cells at the materno-fetal interface, suggesting that it may act as immunomodulator during pregnancy. In this paper, we report that affinity-purified beta2-microglobulin-associated sHLA-G1 triggered apoptosis in activated, but not resting CD8+ peripheral blood cells. We demonstrate by Western blotting that sHLA-G1 enhanced CD95 ligand expression in activated CD8+ cells. Cytotoxicity was inhibited by preincubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
281
4
7

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 424 publications
(303 citation statements)
references
References 29 publications
10
281
4
7
Order By: Relevance
“…In particular, soluble HLA-G induces apoptosis of CD8 + T and NK cells and may participate in allograft tolerance through peripheral deletion of alloreactive T cells after allotransplantation in vivo [21,22]. Previous analysis of the functional role of both HLA-G1 and HLA-G5 in mixed lymphocyte reaction showed that both suppress the alloproliferative response of T cells [23,24,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, soluble HLA-G induces apoptosis of CD8 + T and NK cells and may participate in allograft tolerance through peripheral deletion of alloreactive T cells after allotransplantation in vivo [21,22]. Previous analysis of the functional role of both HLA-G1 and HLA-G5 in mixed lymphocyte reaction showed that both suppress the alloproliferative response of T cells [23,24,29].…”
Section: Discussionmentioning
confidence: 99%
“…HLA-G leader peptide stabilizes the cell-surface expression of another non-classical HLA class I inhibitory molecule, HLA-E [20]. Finally, soluble HLA-G induces apoptosis of CD8 + T and NK cells through ligation with CD8, and via a Fas/FasLdependent mechanism [11,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…A role in controlling T cell expansion, blocking CTL activity, and inducing apoptosis in alloreactive T cells has been suggested for soluble HLA-G (19,20,44). Alternatively, soluble Mamu-AG might also help prevent antisperm immune responses following minor breaks in the bloodtestis barrier of the seminiferous basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, soluble HLA-G was detected not only in pregnancy, but also in nonpregnant women as well as males. Recent studies suggested that HLA-G5, one isoform of soluble HLA-G, can induce apoptosis in peripheral CD8 ϩ T cells via a Fas-Fas ligand mechanism (19), can suppress an allogeneic proliferative T cell response in mixed lymphocyte cultures (20), and can inhibit peripheral blood NK cell-mediated cytotoxicity (21). These results collectively suggest that while membrane-bound HLA-G may interact with resident leukocytes within the decidua, soluble HLA-G may act on blood cells in the peripheral circulation in both pregnant and nonpregnant individuals.…”
Section: T He Nonclassical Mhc Class I Molecule Hla-g Has Beenmentioning
confidence: 99%
“…Additional experiments have shown that fragments of amniotic membrane exert immunosuppressive properties in mixed lymphocyte reactions [30].…”
Section: Discussionmentioning
confidence: 99%